2021
DOI: 10.3389/fneur.2021.614636
|View full text |Cite
|
Sign up to set email alerts
|

All Central Nervous System Neuro- and Vascular-Communication Channels Are Surrounded With Cerebrospinal Fluid

Abstract: Background: Recent emerging evidence has highlighted the potential critical role of cerebrospinal fluid (CSF) in cerebral waste clearance and immunomodulation. It is already very well-established that the central nervous system (CNS) is completely submerged in CSF on a macro-level; but to what extent is this true on a micro-level? Specifically, within the peri-neural and peri-vascular spaces within the CNS parenchyma. Therefore, the objective of this study was to use magnetic resonance imaging (MRI) to simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The presence of the meningeal lymphatic vessels was first mentioned by Paolo Mascagni at the end of the 18 th century, re-introduced several times in the 1950s, 1960s, and 1990s, and finally been confirmed in 2015 by Louveau et al (Louveau et al, 2015) and Aspelund et al (Aspelund et al, 2015) (also see the review (Da interstitial wastes and CSF/ISF from the brain parenchyma after they travel through the glymphatic pathway. A similar CSF/ISF clearance mechanism was also found along cranial and spinal nerves (Fahmy et al, 2021;Ma et al, 2017).…”
Section: 21) Ensemble Activity and Diffusing Factorssupporting
confidence: 62%
“…The presence of the meningeal lymphatic vessels was first mentioned by Paolo Mascagni at the end of the 18 th century, re-introduced several times in the 1950s, 1960s, and 1990s, and finally been confirmed in 2015 by Louveau et al (Louveau et al, 2015) and Aspelund et al (Aspelund et al, 2015) (also see the review (Da interstitial wastes and CSF/ISF from the brain parenchyma after they travel through the glymphatic pathway. A similar CSF/ISF clearance mechanism was also found along cranial and spinal nerves (Fahmy et al, 2021;Ma et al, 2017).…”
Section: 21) Ensemble Activity and Diffusing Factorssupporting
confidence: 62%
“…Recently, Krishnamurthy et al (2018) showed the distribution of MRI-labeled dextran along the spinal nerves, suggesting these nerves as the CSF outflow pathways from the spinal subarachnoid space to the lymphatics via perineural routes; as well as exit along the perineural spaces of cranial nerves (CNI, CNII, and CNV). In a previous study, we have demonstrated that all 12 pairs of cranial nerves and all 31 pairs of spinal nerves are surrounded with CSF in humans, which drain to regional peripheral lymphatics (Fahmy et al, 2021).…”
Section: Other Perineural Spacesmentioning
confidence: 93%
“… 13 More recently, based on findings in five participants, another MRI study suggested that all peri-neural spaces surrounding cranial nerves were filled with CSF. 14 Collectively, since the existence of peri-neural pathways in humans is still controversial, studies have rarely reported the function of these pathways, or their potential interactions with sleep quality and cognitive function.…”
Section: Introductionmentioning
confidence: 99%